2022
DOI: 10.1186/s13690-022-00917-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of technical quality of antenatal and perinatal services in a nationally representative sample of health facilities in Nepal

Abstract: Background Access to routine antenatal and perinatal services is improved in the last two decades in Nepal. However, gaps remain in coverage and quality of care delivered from the health facilities. This study investigated the delivery of technical quality antenatal and perinatal services from health facilities and their associated determinants in Nepal. Methods Data for this study were derived from the Nepal Health Facility Survey 2015. The World … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Nepal Health Facility Survey (NHFS) revealed that only four out of 10 health facilities had carried out neonatal resuscitation and only 3% of Primary Health Care Centers (PHCCs) had performed all basic emergency obstetric signal functions at least once in the three months preceding the survey [19]. To improve the quality of perinatal care, a recent study indicated the need of implementing tailored strategies, including recruitment of health worker, supervision and onsite coaching and access to necessary equipment and medicine in health facilities [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nepal Health Facility Survey (NHFS) revealed that only four out of 10 health facilities had carried out neonatal resuscitation and only 3% of Primary Health Care Centers (PHCCs) had performed all basic emergency obstetric signal functions at least once in the three months preceding the survey [19]. To improve the quality of perinatal care, a recent study indicated the need of implementing tailored strategies, including recruitment of health worker, supervision and onsite coaching and access to necessary equipment and medicine in health facilities [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, women from low-income households, rural areas, and ethnic minority groups are more likely to experience poor health outcomes and have limited access to healthcare services [ 23 ]. Recent studies also show that women utilize quality MNH services with better health facility capacity, especially the private ones since they provide better quality health services [ 29 , 30 ]. While the existing studies have noted a decrease in MCH service inequality between 2011 and 2016, the drivers of such decline are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The facility readiness domain covers four sub-domains for both services: general readiness (e.g., water, electricity), equipment (e.g., delivery beds for childbirth services), medicine/commodities (e.g., misoprostol, magnesium sulphate, iron tablets), and staff and guidelines (e.g., availability of protocols, guidelines for training). Based on national guidelines for maternal and newborn care [36], and availability of information in the dataset [28], we contextualised and extracted information for the domain and subdomain-specific items for structural quality of health facility for MNH services taking reference of previous studies [13,28,34,36,37]. Based on the information available in dataset, a number of domain and sub-domain-specific items were identified to calculate the structural quality scores of health facilities for ANC, and perinatal services (Tables A and B in S1 File).…”
Section: Outcome Variables and Measurementmentioning
confidence: 99%